A V-Band Wideband Power Amplifier with High Gain in a 130 nm SiGe BiCMOS Process - Jianing Hu; Jialong Wan; Yi Shen; Wei Zhao; Jiang Luo (Micromachines)
This paper introduces a high-gain wideband power amplifier (PA) designed for V-band applications, operating across 52 to 65 GHz. The proposed PA design employs a combination of techniques, including pole-gain distribution, base-capacitive peaking, and the parallel configuration of multiple small-sized transistors. These strategies enable significant bandwidth extension while maintaining high gain, substantial output power, and a compact footprint. A two-stage PA using the combination technique was developed and fabricated in a 130 nm SiGe BiCMOS process. The PA prototype achieved a peak gain of 27.3 dB at 64 GHz, with a 3 dB bandwidth exceeding 13 GHz and a fractional bandwidth greater than 22.2%. It delivered a maximum saturated output power of 19.7 dBm and an output 1 dB compression point of 18 dBm. Moreover, the PA chip occupied a total silicon area of 0.57 mm2, including all testing pads with a compact core size of 0.198 mm2.